2020
DOI: 10.31895/hcptbn.15.3-4.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of accelerated solvent extraction conditions on the isolation of bioactive compounds from fennel (Foeniculum vulgare Mill.) seeds

Abstract: This study focused to establish the optimal conditions of accelerated solvent extraction (ASE), i.e., temperature, static extraction time and number of extraction cycles, for the isolation of fennel (Foeniculum vulgare Mill.) seeds phenols and pigments using 96% ethanol as an extraction solvent. Hence, extraction conditions of temperature (80 and 110 °C), static extraction time (5 and 10 min) and number of extraction cycle (1, 2, 3 and 4) were varied. Obtained extracts were spectrophotometrically analyzed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…TPC of MAE extracts ranged from 237.3 ± 10.5 to 706.2 ± 19.0 mg GAE/100 g, which is in agreement with the results of Roby et al (2013) [32], where maceration during 72 h was applied. Repajić et al (2020) [33] reported lower TPC values (145.27-474.21 mg GAE/100 g) for the extractions performed with pressurized liquid extraction. Higher TPC was reported in methanolic and ethanolic fennel seed extracts from Pakistan (627.21 ± 18.36-967.50 ± 35.51 mg GAE/100 g) [34] and in methanolic extracts from Iran and Europe (14 ± 0.18-262 ± 0.91 mg/g of dry weight (dw) [35], both isolated by maceration during 8 and 24 h, respectively.…”
Section: Mae Optimizationmentioning
confidence: 97%
“…TPC of MAE extracts ranged from 237.3 ± 10.5 to 706.2 ± 19.0 mg GAE/100 g, which is in agreement with the results of Roby et al (2013) [32], where maceration during 72 h was applied. Repajić et al (2020) [33] reported lower TPC values (145.27-474.21 mg GAE/100 g) for the extractions performed with pressurized liquid extraction. Higher TPC was reported in methanolic and ethanolic fennel seed extracts from Pakistan (627.21 ± 18.36-967.50 ± 35.51 mg GAE/100 g) [34] and in methanolic extracts from Iran and Europe (14 ± 0.18-262 ± 0.91 mg/g of dry weight (dw) [35], both isolated by maceration during 8 and 24 h, respectively.…”
Section: Mae Optimizationmentioning
confidence: 97%
“…Seeds contain several lipophilic and hydrophilic compounds like carotenoids, phenols, chlorophylls, unsaturated fatty acids, and phytosterols. These compounds act as potential antioxidant agent and prevent various types of diseases [ 760 ]. The major phytoconstituents of fennel seeds are volatile aroma compounds, phenols, and phenolic glycosides like trans-anethole (81.63% and 87.85%), fenchone, and estragole.…”
Section: Bioactive Potential Of Selected Spices and Herbsmentioning
confidence: 99%
“…Studies have shown that water content increases the extraction efficiency of polyphenolics, because the contact area between the substance and the solvent increases due to the swelling effect of water on plant tissue [15]. Recently, scientists have also investigated the application of unconventional extraction techniques such as microwave-assisted extraction (MAE) [16][17][18], ultrasound-assisted extraction (UAE) [19,20], pressure-assisted liquid extraction (PLE) [21,22], supercritical CO 2 extraction (SC-CO 2 ) [23,24], pulsed electric field (PEF)-assisted extraction [25,26], and enzyme-assisted extraction (EAE) [27][28][29] compared to conventional solvent extraction (CSE) methods, such as Soxhlet extraction, decoction, maceration, infusion, percolation, digestion, serial exhaustive extraction, and simple mixing, due to their numerous advantages [13]. These new techniques are considered to be environmentally friendly extraction methods and are therefore suitable for application.…”
Section: Introductionmentioning
confidence: 99%